2008
DOI: 10.1128/jcm.02071-07
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the BD GeneOhm Methicillin-Resistant Staphylococcus aureus (MRSA) PCR Assay to Culture by Use of BBL CHROMagar MRSA for Detection of MRSA in Nasal Surveillance Cultures from an At-Risk Community Population

Abstract: We compared the BD GeneOhm methicillin-resistant Staphylococcus aureus (MRSA) PCR assay to culture with BBL CHROMagar MRSA for nasal surveillance among 602 arrestees from the Baltimore City Jail. The sensitivity and specificity were 88.5% and 91.0%, respectively, and after secondary analysis using enrichment broth, they were 89.0% and 91.7%, respectively. Twenty-three of 42 false-positive PCR lysates contained methicillin-susceptible S. aureus.Recent community-associated methicillin-resistant Staphylococcus au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
38
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 19 publications
8
38
1
Order By: Relevance
“…The utility of these tests, such as the BD GeneOhm MRSA assay (BD-MRSA PCR; BD GeneOhm, San Diego, CA), has been described in numerous publications (2,3,6,17,25). However, performance issues related to "falsepositive" results have been reported by some investigators (2,3,21).…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…The utility of these tests, such as the BD GeneOhm MRSA assay (BD-MRSA PCR; BD GeneOhm, San Diego, CA), has been described in numerous publications (2,3,6,17,25). However, performance issues related to "falsepositive" results have been reported by some investigators (2,3,21).…”
mentioning
confidence: 95%
“…During an epidemiological study performed on adults that compared chromogenic media and the BD-MRSA PCR for detection of MRSA from anterior nasal specimens (5), 23 MSSA isolates were recovered that were initially identified as MRSA positive by the BD-MRSA PCR in which no MRSA was recovered (6). Isolates (n ϭ 23) were recovered directly from subculture of the enrichment Trypticase soy broth with 6.5% NaCl.…”
Section: S Aureus Isolatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight of the 27 PCR-positive/culture-negative wound specimens contained methicillin-sensitive S. aureus (MSSA), a fact which has been observed also by others. For instance, Farley et al (12) reported that 55% of the falsepositive PCR specimens contained MSSA, some of the MSSA lysates being, again, positive upon repeated PCR testing. Likewise, Desjardins et al (9) reported a false-positive PCR result with an MSSA strain (ATCC 25923) carrying an element similar to SCCmec which was inserted in the same integration site as SCCmec.…”
mentioning
confidence: 99%
“…To control the transmission of MRSA in health care facilities, targeted active surveillance cultures and an active infection control program to eliminate or control the spread of MRSA in hospitals are recommended (1,2). The introduction of molecular methods (e.g., PCR) for the detection of MRSA in nasal specimens has improved the reporting time of MRSA and utilization of infection control resources (3)(4)(5). However, not all laboratories can justify the added expense of molecular methods.…”
mentioning
confidence: 99%